2016
DOI: 10.1038/nmicrobiol.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Speciation driven by hybridization and chromosomal plasticity in a wild yeast

Abstract: Hybridization is recognized as a powerful mechanism of speciation and a driving force in generating biodiversity. However, only few multicellular species, limited to a handful of plants and animals, have been shown to fulfil all the criteria of homoploid hybrid speciation. This lack of evidence could lead to the interpretation that speciation by hybridization has a limited role in eukaryotes, particularly in single-celled organisms. Laboratory experiments have revealed that fungi such as budding yeasts can rap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
273
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(292 citation statements)
references
References 48 publications
18
273
1
Order By: Relevance
“…A recent review found that 11% of species across 47 plant genera were likely of allopolyploid origin (Barker et al, 2016). Meanwhile, only a handful of examples of homoploid hybrid speciation have been identified in animals (Mavárez et al, 2006;Lukhtanov et al, 2015), fungi (Leducq et al, 2016), and plants (Rieseberg et al, 2003a). In agreement with the paucity of well-supported examples, simulations suggest that hybridization more likely results in stable hybrid zones or the extinction of a parental species than homoploid hybrid speciation (Buerkle et al, 2003).…”
Section: Hybrid Speciationmentioning
confidence: 97%
“…A recent review found that 11% of species across 47 plant genera were likely of allopolyploid origin (Barker et al, 2016). Meanwhile, only a handful of examples of homoploid hybrid speciation have been identified in animals (Mavárez et al, 2006;Lukhtanov et al, 2015), fungi (Leducq et al, 2016), and plants (Rieseberg et al, 2003a). In agreement with the paucity of well-supported examples, simulations suggest that hybridization more likely results in stable hybrid zones or the extinction of a parental species than homoploid hybrid speciation (Buerkle et al, 2003).…”
Section: Hybrid Speciationmentioning
confidence: 97%
“…We used genomes from 24 strains that are structured in three main lineages named SpA, SpB and SpC (Charron et al 2014; Leducq et al 2016). Two S. cerevisiae strains were included as outgroups: the wild isolate YPS128 (Sniegowski et al 2002;Peter et al 2018) and the reference strain S288C.…”
Section: A Large Number Of Intergenic Orfs Segregates In Wild S Paramentioning
confidence: 99%
“…Two S. cerevisiae strains were included as outgroups: the wild isolate YPS128 (Sniegowski et al 2002;Peter et al 2018) and the reference strain S288C. These lineages cover different levels of nucleotide divergence, ranging from ~ 13 % between S. cerevisiae and S. paradoxus to ~2.27 % between the two closest SpB and SpC lineages (Kellis et al 2003;Leducq et al 2016). We used microsynteny to identify and align homologous non-genic regions between pairs of conserved annotated genes ( Fig.…”
Section: A Large Number Of Intergenic Orfs Segregates In Wild S Paramentioning
confidence: 99%
See 2 more Smart Citations